A Note on Some Numerical Approaches to Solve a θ˙ Neuron Networks Model - Samir Kumar Bhowmik; Feras M. Al Faqih; Md. Nazmul Islam (Abstract and Applied Analysis)
Space time integration plays an important role in analyzing scientific and engineering models. In this paper, we consider an integrodifferential equation that comes from modeling θ˙ neuron networks. Here, we investigate various schemes for time discretization of a theta-neuron model. We use collocation and midpoint quadrature formula for space integration and then apply various time integration schemes to get a full discrete system. We present some computational results to demonstrate the schemes.